Anthropogenic dark earth: Evolution, distribution, physical, and chemical properties - Asare, Michael O. (European journal of soil science, 2022)
Anthropogenic dark earth (ADE) is a category of Anthrosols (anthropogenic soils) characterised by dark colour from homogeneous charcoal inclusion and extraordinary fertility compared with non‐anthropogenic soils. The study aims to provide a detailed overview of the origin and distributions of ADEs, together with their physical and chemical characteristics, to reveal their fertility status for arable land use. According to this study, most studied ADEs are well distributed in tropical (Amazonian and African dark earth) and temperate (European dark earth) climatic regions. Middens are localised, with large‐sized ones well preserved in the Arctic region due to the wet and cold weather conditions. The formation of ADE is mainly associated with deliberate and unintentional ancient human activities: deposition of domestic and occupational wastes, charred residues, biomass ashes, burning, and fertilisation of fields. The characteristic dark colour of ADE resulted mainly from charcoal and the decomposition of organic wastes. The material composition of ADEs (including charcoal, organic matter, and clay) contributes to the formation of sizable pores for the retention of water and elements and aeration. ADE exhibits a C:N ratio for good mineralization, stable organic matter stock, and higher cation exchange capacity. Additionally, ADEs are characterised by circum‐neutral reactions and enriched by nutrients (C, N, P, Ca, Mg, Mn, Cu, Zn, Mn, and Fe) and other elements (Sr, Rb, and Ba) compared with surrounding non‐anthropogenic soils. Although generally highly productive, a comparison of herbage production and crop yields between ADEs and natural soils is not well studied. The persistence of anthropogenic activities that lead to the formation of ADE indicates that these soils are still subject to continuous development, especially in rural settings. Adopting the process of ADE development in recent arable land can represent a promising future for sustainable agriculture. Highlights Anthropogenic dark earths (ADEs) are characterized by their physical and chemical signatures. Characteristic high pore size of ADEs due to charcoal inclusion support the retention of nutrients. ADEs are often have reduced acidity and high C, N, P, Ca, Mg, Mn, Cu, Zn, Mn, and Fe contents. ADEs represent an archive of fertile soils suitable for sustainable agriculture.